Students feedback on the new task-based logbook used in family medicine posting in Universiti Sultan Zainal Abidin, Terengganu, Malaysia - Norwati, Daud; Nurulhuda, Mat Hassan; Siti Norazlina, Juhari (2018)
Background: The typical logbook used in undergraduate medical programme usually records the cases seen and clinical procedures done by medical students. For the 2017/2018 session, a new task-based logbook was used to replace the old logbook which only records patients’ clinical summary. There were 17 tasks which covered common problems in primary care. It included patient’s summary and related questions on the areas of chronic disease, women’s health, child health and preventive care. Students were expected to find the selected problems and answer the questions. At the end of the posting, a short VIVA was done based on the logbook. This short survey was to assess the students’ feedback on the new task-based logbook to assist learning during family medicine posting. Method: At the end of the posting, feedback was obtained regarding the new logbook. There were 4 questions; 1. It was useful to guide students, 2. It was more effective to help learn theoretical knowledge, 3. It was more effective to help learn clinical skills and 4. It was time consuming to complete. The response was in the form of scale from 1 to 5, from ‘strongly disagree’ to ‘strongly agree’. Data was analysed for mean and standard deviation. Results: By December 2017, half of year 4 students have done family medicine posting. Response rate was 85% (25/29). The mean (SD) for questions 1,2,3 and 4 were 4.32 (0.90), 4.44 (0.92), 4.36 (0.81) and 3.84 (0.99) respectively. Conclusion: Students perceived that the new logbook is useful and more effective in guiding them to learn family medicine than the old logbook. However, it is time consuming to complete. The logbook may need to be improved to suit medical students’ time.